2009
DOI: 10.1007/s10493-009-9316-5
|View full text |Cite
|
Sign up to set email alerts
|

The effects of spiromesifen on life history traits and population growth of two-spotted spider mite (Acari: Tetranychidae)

Abstract: Laboratory bioassays were conducted to evaluate the effects of spiromesifen on gross fecundity, gross fertility, net fertility and population growth of two-spotted spider mite (Tetranychus urticae Koch) after treatments with four acaricide concentrations: 180 mg/l, i.e. maximum recommended concentration for use in glasshouses against spider mites, 18, 1.8, and 0.18 mg/l, i.e. concentration discriminative for eggs and immatures in preliminary studies which produced 100% mortality of these stages. Quiescent fema… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
0
1

Year Published

2011
2011
2015
2015

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 35 publications
(18 citation statements)
references
References 22 publications
(25 reference statements)
4
12
0
1
Order By: Relevance
“…Also, significantly higher reduction percentages of fertility were registered in the second assay, as well as a more pronounced reduction of r i values, with population decline which was caused by higher concentrations of spirotetramat. Similar pattern was previously reported for spiromesifen (Marcic et al 2010a). …”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Also, significantly higher reduction percentages of fertility were registered in the second assay, as well as a more pronounced reduction of r i values, with population decline which was caused by higher concentrations of spirotetramat. Similar pattern was previously reported for spiromesifen (Marcic et al 2010a). …”
Section: Discussionsupporting
confidence: 91%
“…Moreover, the same symptomology of poisoning described previously for these two tetronic acid derivatives (Wachendorff et al 2002;Nauen et al 2005;Marcic 2007;van Pottelberge et al 2009;Marcic et al 2010a) was observed for spirotetramat, which points to the same mode of action of these three compounds on spider mites. Much stronger action of spirotetramat was registered on females treated at preovipositional period, compared to females treated at teleiochrysalis stage.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations